Implementasi Metode Certainty Factor pada Identifikasi Kerusakan Kendaraan Bermotor Roda Dua - Gaung Rimba Putra Dirgantara; Suprapto Suprapto; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The purpose of this study is to help motorcycle riders and mechanics to identify the breakdowns of motorcycle based on symptoms. Limited number of experts to repair the motorcycles will spend long time to identify and repair the motorcycles. Hence, this study is done to make an application system to identify the breakdowns of motorcycle with Certainty Factor methods. The evaluation of this study use the testing scenario that compare the value of accuracy from the result of the expert questionnaires with application system. On the test, obtained the value of accuracy that is pretty good with 73,3%. This value proves that this study still have opportunities to be developed even further.